Crystal engineering of porous coordination networks for C3 hydrocarbon separation. (29th December 2020) - Gao, Mei‐Yan; Song, Bai‐Qiao; Sensharma, Debobroto; Zaworotko, Michael J.
Abstract: C3 hydrocarbons (HCs), especially propylene and propane, are high‐volume products of the chemical industry as they are utilized for the production of fuels, polymers, and chemical commodities. Demand for C3 HCs as chemical building blocks is increasing but obtaining them in sufficient purity (>99.95%) for polymer and chemical processes requires economically and energetically costly methods such as cryogenic distillation. Adsorptive separations using porous coordination networks (PCNs) could offer an energy‐efficient alternative to current technologies for C3 HC purification because of the lower energy footprint of sorbent separations for recycling versus alternatives such as distillation, solvent extraction, and chemical transformation. In this review, we address how the structural modularity of porous PCNs makes them amenable to crystal engineering that in turn enables control over pore size, shape, and chemistry. We detail how control over pore structure has enabled PCN sorbents to offer benchmark performance for C3 separations thanks to several distinct mechanisms, each of which is highlighted. We also discuss the major challenges and opportunities that remain to be addressed before the commercial development of PCNs as advanced sorbents for C3 separation becomes viable. Abstract : The study of porous coordination networks (PCNs) for their ability to purify C3 hydrocarbons (HCs) represents a subject of growing interest thanks to the potential for reduction of the energy footprint of these high‐volume energy‐intensive separations. This review highlights recent advances in our understanding of sorbent‐sorbate binding in PCNs and how this has enabled the setting of new benchmarks for separation performance, setting the stage for further improvements.